Two new Peruvian species of Tichocoelidia Kramer (Hemiptera: Cicadellidae: Neocoelidiinae) with a key to males - Gonçalves, Clayton Corrêa; Barbosa, Julianna Freires (Zootaxa, 2021)
Two new species of Tichocoelidia Kramer, 1962 are described and illustrated, T. marceloi sp. nov. and T. vanessae sp. nov., both from Cusco, Peru. A key to males of the four known species of Tichocoelidia is provided.